Ruthenium complexes bearing an unsymmetrical pincer ligand with a 2-hydroxypyridylmethylene fragment: active catalysts for transfer hydrogenation of ketones. Issue 11 (12th February 2016) - Shi, Jing; Hu, Bowen; Gong, Dawei; Shang, Shu; Hou, Guangfeng; Chen, Dafa
Abstract : The synthesis, reactivity and catalytic transfer hydrogenation activity of three metal–ligand cooperative ruthenium(ii ) complexes (3–5 ) with a 2-hydroxypyridylmethylene fragment are reported. Abstract : Five ruthenium(ii ) complexes were synthesized, including (HO-C5 H3 N-CH2 -C5 H3 N-C5 H4 N)Ru(PPh3 )Cl2 (3 ), [(HO-C5 H3 N-CH2 -C5 H3 N-C5 H4 N)Ru(PPh3 )2 Cl][PF6 ] (4 ) and [(HO-C5 H3 N-CH2 -C5 H3 N-C5 H4 N)Ru(PPh3 )2 OH][PF6 ] (5 ) bearing an unsymmetrical pincer NNN ligand with a 2-hydroxypyridylmethylene fragment, and [(CH3 O-C5 H3 N-CH2 -C5 H3 N-C5 H4 N)2 Ru][Cl]2 (6 ) and [(CH3 O-C5 H3 N-CH2 -C5 H3 N-C5 H4 N)2 Ru][PF6 ]2 (7 ) containing 2-methoxypyridylmethylene moieties.4 reacts with H2 O at room temperature to give5 whose crystal structure reveals the existence of intramolecular hydrogen-bonding between its two –OH groups.3 exhibits high catalytic activity for transfer hydrogenation of ketones.